Depressive symptoms in higher education students during the first wave of the COVID-19 pandemic. An examination of the association with various social risk factors across multiple high- and middle-income countries. (December 2021) - Van de Velde, S.; Buffel, V.; van der Heijde, C.; Çoksan, S.; Bracke, P.; Abel, T.; Busse, H.; Zeeb, H.; Rabiee-khan, F.; Stathopoulou, T.; Van Hal, G.; Ladner, J.; et al.
Abstract: Higher-education students face substantial risks for developing depressive symptoms during the COVID-19 pandemic or experiencing exacerbated pre-existing depressive symptoms. This study uses data from the COVID-19 International Student Well-Being Study, which collected data through a non-representative convenience sample in 125 higher-education institutions (HEI) across 26 high- and middle-income countries (N: 20, 103) during the first wave of the COVID-19 pandemic. It describes the prevalence of depressive symptoms in higher-education students. We find substantial cross-national variation in depressive symptoms, with lowest mean levels established in the Nordic countries and France, while highest mean levels of depressive symptoms were found in Turkey, South Africa, Spain and the USA. Elevated risk for depressive symptoms was found in female students, students with fewer social support resources and in a more disadvantaged socioeconomic position, and students with a migrant background. COVID-19 related stressors, such as reduced social contact, increased financial insecurity, and academic stress explained a relatively larger proportion of the variance in depressive symptoms compared to non-COVID-19 related stressors. This finding shows that not the pandemic itself, but rather the secondary effects of the pandemic relate to students' mental health. Our results enable HEIs to be better equipped to target groups that are particularly at risk during a pandemic. Highlights: Exacerbated depressive symptoms are observed among students during the COVID-19 pandemic. Depressive symptoms in students vary across countries during the COVID-19 pandemic. Depressive symptoms related more strongly to COVID-19 than to non-COVID-19 stressors.